THE INFLUENCE OF COMPETENCE AND EDUCATION ON EMPLOYEE PERFORMANCE WITH JOB PROMOTION AS AN INTERVENING VARIABLE AT PT PLN (PERSERO) UP3 NORTH MEDAN - Agus Naini Siregar; Kiki Farida Ferine; Muhammad Isa Indrawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of competence and education on employee performance with job promotion as an intervening variable at PT PLN (Persero) UP3 North Medan. This study is motivated by the importance of improving employee performance which is not only influenced by individual abilities, but also by job promotion opportunities as a form of appreciation and career development. The research method used is a quantitative approach with data collection techniques through questionnaires. The number of respondents in this study was 69 employees selected through a purposive sampling method. Data analysis was carried out using Partial Least Square (PLS-SEM) to test direct and indirect relationships between variables. The results of the study indicate that: (1) competence has a positive and significant effect on employee performance, (2) competence has a positive and significant effect on job promotion, (3) education does not have a significant effect on employee performance, (4) education has a positive and significant effect on job promotion, (5) job promotion has a positive and significant effect on employee performance, (6) job promotion mediates the effect of competence on employee performance, and (7) job promotion also mediates the effect of education on employee performance. Thus, it can be concluded that competence and education are important factors in supporting job promotion, while job promotion is proven to be a key variable that improves employee performance at PT PLN (Persero) UP3 North Medan.